2019
DOI: 10.1007/s13198-019-00803-y
|View full text |Cite
|
Sign up to set email alerts
|

System availability assessment using a parametric Bayesian approach: a case study of balling drums

Abstract: Assessment of system availability usually uses either an analytical (e.g., Markov/semi-Markov) or a simulation approach (e.g., Monte Carlo simulation-based). However, the former cannot handle complicated state changes and the latter is computationally expensive. Traditional Bayesian approaches may solve these problems; however, because of their computational difficulties, they are not widely applied. The recent proliferation of Markov Chain Monte Carlo (MCMC) approaches have led to the use of the Bayesian infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Table 2 presents parameters of distributions (Weibull, exponential or lognormal) and 95% confidence intervals, the expected values, and availabilities calculated after the models. Considering the exponential as a particular case of the Weibull distribution, the findings are consistent with Saari et al (2019), who reported a case in the mining industry in which the Weibull and lognormal are the most likely distributions to fit respectively TBF and TTR. In our case, when the Weibull model fits, the availability did not differ from the previous, simpler calculation.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Table 2 presents parameters of distributions (Weibull, exponential or lognormal) and 95% confidence intervals, the expected values, and availabilities calculated after the models. Considering the exponential as a particular case of the Weibull distribution, the findings are consistent with Saari et al (2019), who reported a case in the mining industry in which the Weibull and lognormal are the most likely distributions to fit respectively TBF and TTR. In our case, when the Weibull model fits, the availability did not differ from the previous, simpler calculation.…”
Section: Resultssupporting
confidence: 87%
“…Ribeiro et al (2019) reported a case in which the overall Av of a serial production line of an auto parts manufacturer ranged between 94% and 98%. Saari et al (2019) reported a study in which the Av of five individual balling drums in the mining industry ranged between [92% and 96%]. As the five machines form a parallel array, the systemic Av overcomes 99%.…”
Section: Resultsmentioning
confidence: 99%